1996
DOI: 10.1002/(sici)1098-2744(199604)15:4<284::aid-mc6>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis suppressed, but tumorigenicity and local invasiveness unaffected, in the human melanoma cell line MelJuSo after introduction of human chromosomes 1 or 6

Abstract: Progression of human melanoma toward increasing malignant behavior is associated with several nonrandom chromosomal aberrations, most commonly involving chromosomes 1, 6, 7, 9, and 10. We previously showed that introduction of human chromosome 6 into the highly metastatic human malignant melanoma cell line C8161 completely suppressed metastasis without altering tumorigenicity (Welch DR, Chen P, Miele ME, et al., Oncogene 9:255-262, 1994). Alterations of chromosome 1 are the most frequent chromosome abnormality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0
6

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 47 publications
3
67
0
6
Order By: Relevance
“…p21-treatment induced G 1 arrest, as expected, but did not interfere with the capability of glioma cells to invade. Interestingly, micro-cell mediated transfer of chromosome 6, where the p21 gene is located, to human melanoma cells did not modify their invasiveness in vitro or in vivo (Welch et al, 1993;Miele et al, 1996). These data are consistent with a previous study showing that transfer of the Rb cDNA to cancer cells decrease their invasiveness in a cell-cycle independent way (Li et al, 1996).…”
Section: Discussionsupporting
confidence: 82%
“…p21-treatment induced G 1 arrest, as expected, but did not interfere with the capability of glioma cells to invade. Interestingly, micro-cell mediated transfer of chromosome 6, where the p21 gene is located, to human melanoma cells did not modify their invasiveness in vitro or in vivo (Welch et al, 1993;Miele et al, 1996). These data are consistent with a previous study showing that transfer of the Rb cDNA to cancer cells decrease their invasiveness in a cell-cycle independent way (Li et al, 1996).…”
Section: Discussionsupporting
confidence: 82%
“…This fact was overlooked by some researchers. In a recent report, Miele et al (1995) claimed that transfection of MnSOD did not suppress tumorigenicity and metastasis of human melanoma C8161 cells. In this study, the authors showed an increase in MnSOD mRNA, but less than a 1.6-fold increase or a slight decrease in MnSOD protein in two transfectant clones and no increase in MnSOD activity using a native gel assay.…”
Section: Discussionmentioning
confidence: 99%
“…Cell transformation is not always followed by the ability of the tumor cells to metastasize (Miele et al, 1996). In fact, not all the known oncogenes are able to induce the metastatic phenotype in addition to the tumorigenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Oncogenic transformation is the ®rst step for the generation of tumors, but it is not always associated with the metastatic phenotype suggesting that dierent proteins may be implicated in the induction of tumorigenic and metastatic behavior of the tumor cells (Miele et al, 1996). It has been suggested that Rho proteins, in addition to their ability to induce cell transformation may have a role in metastasis.…”
Section: Introductionmentioning
confidence: 99%